f−1(x) = The quantity of five x plus three, over two
f−1(x) = The quantity of five x minus three, over two
f−1(x) = Five over the quantity of two x plus three
f−1(x) = Five over the quantity of three minus two x
2 Answers

Let y = f (x) and g (y) = x
y = (2x + 3) / 5
5y = 2x + 3
x = [ 5y – 3 ] / 2
g (y) = [ 5y – 3 ] / 2
g (x) = [ 5x – 3 ] / 2_____inverse function

Let f(x) = y
Hence
y = (2x + 3) / 5
5y = 2x + 3
2x = 5y – 3
x = (5y 3) / 2
‘Swop’ the letters
y = (5x – 3) / 2
f^1(x) = (5x – 3)/2
Hence second statement is the answer!!!!